The Dilemma Of Indonesia’s Coal Policy In 2020-2060: A Modality Of State Revenue - Andreas Tedy Mulyono; Eka N.A.M. Sihombing (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Coal commodity management policies in Indonesia are closely related to efforts to reduce carbon emissions and increase carbon sequestration. This has the potential to create regulatory synchronization problems because it relates to sectoral challenges from the relevant ministries and/or agencies. To describe the synchronization problem, this research uses a normative juridical method with a statute approach and a conceptual approach. The results of this study are that there are three ministries that are directly or indirectly related to coal management, namely the Ministry of Energy and Mineral Resources, the Ministry of Environment and Forestry, and the Ministry of Finance. The conclusion is that although the 2005-2025 national development target has been announced by the Government, particularly regarding the NZE2060 target, it turns out that the implementation of the regulations in the three ministries has experienced predicaments that have resulted in a dilemma of synchronizing the national climate policy. However, short-term policies implicitly indicate the modality of state revenue as a priority